Statement by the Managing Director on the Independent Evaluation Office Report on IMF Advice on Capital Flows Executive Board Meeting September 18, 2020. (Policy Papers; Policy Paper ;, 2020)
As noted in the report, the adoption of the IV represented a major advance in the IMF's policy framework to provide advice on capital account liberalization and the management of capital flows. Before the adoption of the IV, there was no consistent framework to guide policy advice on these areas. The IV was a major step towards filling the gap existing at the time. It welcomed the economic benefits of capital flows while recognizing the risks associated with capital flow volatility, developed a playbook for safe capital account liberalization, and incorporated capital flow management measures (CFMs) into the policy toolkit. It also noted the importance of international cooperation on capital flow policies in allowing countries to harness the benefits of capital flows safely, while minimizing negative spillovers. It was a demonstration of the institution's flexibility and willingness to embrace theoretical advances and lessons from experience.